The effects of social media marketing on the online purchasing behavior of generation Z consumers in Tacloban City with brand awareness as mediator - Carilla, Hughdz C.; Pilapil, Kurt A.; Plaza, Jybrialane L.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College 2024., 2024)
Nowadays, social media has millions of users and is almost everywhere. With this, several businesses have used it as a platform for marketing their products and services offered. However, some businesses still fail to utilize the effectiveness of social media in terms of its influence on consumers. This research study sheds more light on the effectiveness of Social Media Marketing towards the Online Purchasing Behavior of Generation Z consumers of Tacloban City. A third variable, Brand Awareness, was added and served as a mediator between the relationship of Social Media Marketing and Online Purchasing Behavior. The study employed a quantitative research design with a purposive and snowball sampling method. The study analyzed the demographic profiles, exposure to social media marketing, width and depth of brand awareness, and online purchasing behavior of two hundred and sixteen (216) respondents. A mediation analysis that consists of a series of regression-based analyses was also conducted to measure the strength of the relationships between those three variables. The findings revealed that there is a significant positive relationship between the exposure to social media and the brand awareness of Generation Z consumers. Likewise, there is also a significant positive relationship between the Generation Z consumers' exposure to social media marketing and their online purchasing behavior. Additionally, the mediation analysis conducted between social media marketing, online purchasing behavior, and brand awareness showed that brand awareness partially mediates the relationship between the other two variables. The findings of this study provide valuable insights to owners of both big and small businesses regarding the utilization of digital technologies in marketing the products and services that they offer. Future researchers can expand on this study by tackling other variables that could potentially mediate the relationship between Social Media Marketing and Online Purchasing Behavior. They could also group Generation Z consumers into different age brackets and compare them.
Keywords: Social media marketing -- Tacloban City; Social media; Social media marketing; Digital marketing; Brand awareness; Online purchasing behavior; Online shopping; Mediation analysis; Tacloban city; Generation Z